Toxigenic profiles of clinical Clostridioides difficile in public and private healthcare settings in Gauteng, South Africa - Dr Ben Prinsloo; Miss Hlambani Shirinda; Prof Anthony Smith; Prof Marthie Ehlers (International Journal of Infectious Diseases)
Introduction: Clostridioides difficile infection (CDI) is a serious healthcare-associated infection causing life-threatening infectious diarrhea in hospitalized patients accounting for 20% to 30% of all diarrhoea cases in humans. Clostridioides difficile's main virulence factors are toxin A and toxin B encoded by tcdA and tcdB genes respectively, while hypervirulent strains such as ribotype (RT) 027 (ST1) and RT 078 (ST11) express a third toxin namely the binary toxin which is associated with severe CDI symptoms, the binary toxin is encoded by cdtA and cdtB genes. Methods: In South Africa, a rise in hypervirulent strain RT 027 has been noted in both public and private clinical settings, however, there is no molecular data to understand the circulation of this strain, this is due to culturing constraints as C. difficile is anaerobic therefore making it difficult to culture. A total of 100 clinical stool samples presumptively positive for C. difficile by GeneXpert real-time PCR assay and ELISA were collected from public and private settings. Clostridioides difficile was isolated using a selective medium and multiplex polymerase chain reaction (M-PCR) assays were used to identify and screen for toxigenic C. difficile isolates. Results: The study identified 62 toxigenic C. difficile isolates and 53% (33/62) were from public settings, while 47% (29/62) were from private settings. The most frequent toxin profile was tcdA+, tcdB+, cdtA+, cdtB+ in 26 (42%) followed by tcdA+, tcdB+, cdtAˉ, cdtBˉ in 22 (35%) isolates. The genes encoding CDT (binary toxin) were also found in 37(60%) isolates. Discussion: This study provides a reference point for further epidemiological and genomic surveillance of CDI in South Africa and Africa in general. This study reports for the first time the hypervirulent strain toxin profile (tcdA+, tcdB+, cdtA+, cdtB+) in South Africa. Conclusion: Our data advances our knowledge and pathogenicity characteristics of C. difficile in South Africa. Carefully implementing infection control techniques is necessary to stop the spread of C. difficile strains in hospital settings.